Research progress in the relationship between ultra-processed food intake and pregnancy outcomes - MI Xiaoyang; DING Ying; CHEN Yijing; JIA Jie (Shanghai Jiaotong Daxue xuebao. Yixue ban)
In recent years, the global consumption of ultra-processed foods (UPFs) has increased. UPFs are classified as the fourth group of food in the NOVA classification system: industrially formulated foods made entirely or mostly from substances extracted from foods (oils, fats, sugar, starch, proteins, etc), derivatives of food constituents (hydrogenated fats, modified starches, etc), or multiple food additives. Common manufacturing techniques include extrusion, moulding, and pre-frying. As high-energy-density foods, UPFs are typically characterized by high levels of sugar, fat, and salt, and low levels of dietary fiber, protein, vitamins, and minerals, resulting in low nutrient density. Studies have shown that a high intake of UPFs increases the risk of various chronic diseases. Nutrition during pregnancy is a crucial factor influencing pregnancy outcomes, and balanced and adequate nutrient intake is essential for the health of both the mother and child. Given that UPFs have limited nutritional density, high intake during pregnancy may be detrimental to maternal and infant health. However, the impact of consuming UPFs during pregnancy on maternal and infant health is not extensively studied. This article reviews the literature on the effects of UPFs on pregnancy outcomes, aiming to provide a foundation for further research and personalized dietary guidance.